2015
DOI: 10.1016/j.jviromet.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of protein expression changes of the Vero E6 cells infected with classic PEDV strain CV777 by using quantitative proteomic technique

Abstract: Recent outbreaks of porcine epidemic diarrhea virus (PEDV) have caused widespread concern. The identification of proteins associated with PEDV infection might provide insight into PEDV pathogenesis and facilitate the development of novel antiviral strategies. We analyzed the differential protein profile of PEDV-infected Vero E6 cells using mass spectrometry and an isobaric tag for relative and absolute quantification. A total of 126 proteins were identified that were differentially expressed between the PEDV-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 62 publications
0
34
0
Order By: Relevance
“…The Vero cell-adapted PEDV CV777 strain, kindly provided by Maurice Pensaert at Ghent University (Merelbeke, Belgium), was propagated as previously described (Hofmann and Wyler, 1988;Sun et al, 2015). Briefly, Vero cells were inoculated with the virus at a multiplicity of infection (MOI) of 1 and cultured in serum-free DMEM for 72 h at 37 C with 5% CO 2 .…”
Section: Cells and Virusesmentioning
confidence: 99%
“…The Vero cell-adapted PEDV CV777 strain, kindly provided by Maurice Pensaert at Ghent University (Merelbeke, Belgium), was propagated as previously described (Hofmann and Wyler, 1988;Sun et al, 2015). Briefly, Vero cells were inoculated with the virus at a multiplicity of infection (MOI) of 1 and cultured in serum-free DMEM for 72 h at 37 C with 5% CO 2 .…”
Section: Cells and Virusesmentioning
confidence: 99%
“…Enterovirus A71 (EV-A71) strain BC08 , avian influenza virus (AIV) strain H9-WD (Wang et al, 2016b), canine distemper virus (CDV) strain MD77 (Lan et al, 2005), Newcastle disease virus (NDV) strain Lasota and infectious bronchitis virus (IBV) strain M41 (Li et al, 2013), porcine epidemic diarrhea virus (PEDV) strain CV777 (Sun et al, 2015), VSV strain Indiana (Wang et al, 2016a), HSV-1 strain F (Wang et al, 2011) and HCV strain JFH-1 (Xu et al, 2014) are reproduced in RD, MDCK, Vero, HeLa, Vero, HeLa, HEK293T, HeLa and Huh7.5.1 cells respectively, according to the reports indicated above. GFP-NDV strain NA-1 is generated by inserting an additional transcription cassette coding for the enhanced GFP between the P and M genes of the NDV genome (Wang et al, 2015).…”
Section: Virusesmentioning
confidence: 99%
“…A previous proteomic study indicated that more differentially expressed proteins were mapped to the autophagy pathway, and the microtubule-associated protein 1B, a useful biomarker protein for autophagy was up-regulated in PEDV-infected Vero cells [18]. In addition, our previous study demonstrated that mTOR (the mammalian target of rapamycin) pathway, which was closely associated with cellular autophagy, was down-regulated, and that the autophagy associated protein ATG5 was up-regulated during PEDV infection [19].…”
Section: Introductionmentioning
confidence: 99%